Le Cosmos d'Alexandre von Humboldt et La Tentation de saint Antoine de Gustave Flaubert : deux œuvres de toute une vie - Mary Orr (Flaubert: Revue Critique et Génétique)
In the seventh and final tableau of the Tentation de Saint Antoine of 1874, the famous finale is set in the context of a long, detailed description which has not attracted the critical attention it deserves. This article focuses on the importance of this panorama of the natural world as an intertextual exploration of passages from Kosmos by Alexander von Humboldt. The fact that Flaubert’s Correspondance of 1860 mentions his reading of Humboldt’s works suggests rich lines of investigation between Kosmos – which Humboldt calls the « work of all of life » and the final Tentation de Saint Antoine,which Flaubert was reworking at the same moment. This re-reading of the Tentation through the optic of Humboldt underscores the pivotal position of Kosmos amid the scientific discoveries and texts contemporary to Flaubert, and how these inform the vision of life of his protagonist, Antoine, as scientific and religious.